Penerapan Polikultur Ikan Mas (Cyprinus carpio) dan Ikan Nila (Oreochromis niloticus) dalam Kolam Air Deras untuk Meningkatkan Efisiensi Pakan dan Produksi di Kelompok Upaya Mina, Sumedang - Sofi, Nunung; Yustiati, Ayi (Jurnal Gema Ngabdi, 2025)
The Upaya Mina Group in Banyuasih, Sumedang, cultivates common carp using a running water pond system but faces challenges due to rising feed costs that are not matched by the selling price of fish. This community service activity aims to provide a solution through the implementation of a polyculture system combining common carp and Nile tilapia to improve feed efficiency. The method used involved educational outreach through demonstrations and pilot trials at the group’s aquaculture site. The trial results showed that the polyculture system produced 810 kg of fish with a feed efficiency of 76%. In comparison, the group’s previous monoculture system yielded only 640 kg with a feed efficiency of 59%, despite using the same amount of feed, which was 1 ton. The implementation of the polyculture system increased production by 170 kg and feed efficiency by 17%. Thus, the polyculture system not only boosts production but also offers a practical solution to the problem of high feed costs.